ANALYSIS OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTERPRISES BASED ON FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTITIES (SAK EMKM) IN THE RETAIL SECTOR OF MSMES - Nurhasan Nurhasan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, yet they still face difficulties in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Many MSMEs do not understand or implement these standards effectively, which can impact the accuracy of their financial statements. Therefore, this study is crucial to determine how well retail MSMEs have implemented SAK EMKM and identify barriers. This study also aims to examine the impact of understanding and implementing SAK EMKM on MSME financial performance, identify factors that hinder its implementation, and provide practical suggestions for improving MSME compliance with generally accepted accounting standards. This study uses a mixed-method approach using surveys and interviews. Data were collected through questionnaires distributed to MSME members in the Cikeas Udik Village area, Gunung Putri District, Bogor Regency, as well as in-depth interviews with business owners and accountants. Data analysis was conducted using descriptive statistical methods and correlation tests to examine the relationship between understanding of SAK EMKM and MSME financial performance. Based on the results of a simple linear test using SPSS 26, the output shows that the calculated F value = 8.860 with a significance level of 0.006 <0.05, so the regression model can be used to predict the EMKM SAK Understanding variable or in other words there is an influence of the EMKM SAK Understanding variable (X) on the Financial Performance Variable (Y). From the summary table of the simple linear regression test, the value of the relationship/correlation (R) is 0.490 from the output, a coefficient of determination (R Square) of 0.24 is obtained, which means that the influence of the independent variable (EMKM SAK Understanding) on ​​the dependent variable (Financial Performance) is 24%.